Effects of inflammation on irinotecan pharmacokinetics and development of a best-fit PK model. (25th January 2020) - Chityala, Pavan Kumar; Wu, Lei; Chow, Diana S-L; Ghose, Romi
Abstract: Irinotecan is a chemotherapeutic drug used in the treatment of advanced colorectal cancer and elevated blood concentrations of its active metabolite, SN-38 leads to increased gastrointestinal (GI) toxicity and diarrhea in patients. In this study, we investigated the effects of inflammation on the pharmacokinetics (PK) of irinotecan (CPT-11) and its active metabolite, SN-38. Mice were i.p.-injected with either saline or lipopolysaccharide (LPS) to induce inflammation. After 16 h, irinotecan was administered orally. Blood was collected from the tail vein of mice from 0 to 24 h after dosing. Concentrations of irinotecan, SN-38 and SN-38G were analyzed using LC-MS/MS. The AUC, Cmax, and tmax were derived using WinNonlin® 5.2. A PK model was developed using Phoenix NLME® to describe the PK of irinotecan and SN-38 during inflammation. Results indicated a significant increase in the blood concentrations of irinotecan and SN-38 in mice during inflammation. The AUC of irinotecan and SN-38 in LPS group were 2.6 and 2-folds, respectively, of those in control saline-treated mice. The Cmax of irinotecan and SN-38 in LPS treated mice were 2.4 and 2.3-folds of those in saline-treated mice. The PK model was successfully developed and validated. The best-fit plots of individual PK analysis showed a good correlation between observed and predicted concentrations of irinotecan and SN-38. Together, this study reveals that SN-38 concentrations are elevated during inflammation, which may increase the GI toxicity and diarrhea in patients who receive irinotecan; and the developed PK model can quantitatively describe the PK of irinotecan and SN-38 during inflammation. Highlights: The Effects of Inflammation on Irinotecan (CPT-11) PK were investigated. SN-38 blood concentrations and AUC were increased in mice with inflammation. Entero-hepatic recycling (EHR) was found to increase SN-38 exposure. A best-fit PK model was developed with irinotecan, SN-38, and EHR compartments. The developed model predicts the PK of Irinotecan and SN-38 during inflammation.